Patents and industrialization: An historical overview of the British case, 1624-1907 - Christine MacLeod; Alessandro Nuvolari (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
The aim of this paper is to provide a critical survey of patent systems during the first phase of the industrialization process with a special focus on the British case. Perhaps surprisingly, no consensus has been reached yet as to whether the emergence of modern patent systems exerted a favourable impact on inventive activities in this historical phase. However, the recent literature has shed light on a number of fundamental factors affecting the links between inventive activities and the patent system. The concluding section of the paper outlines some history lessons for the current debate on the role of patent in economic development.
Keywords: 330